Faktor-Faktor Yang Mempengaruhi Profitabilitas Perusahaan Manufaktur Sektor Industri Barang Konsumsi - Theresia Jacqueline Audelia, Sufiyati (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence regarding the effect of company size, liquidity, leverage, working capital turnover, and the period of debt deferral towards profitability in consumer goods manufacturing companies listed on Indonesia Stock Exchange in 2015 - 2017. The sampling method used is purposive sampling. The number of samples used is 36 companies in the consumer goods industry sector listed on the Stock Exchange in 2015 - 2017 that meet the specified criteria with data count 108. The data used secondary data in the form of financial statements. The program used to process research data is Eviews 10. The results of the study show that working capital turnover (WCT) has a significant negative effect on profitability. On the other hand, company size (SIZE), liquidity (CR), solvency (DAR), and the period of debt deferral (PDP) did not significantly influence profitability